Biosocial perspectives on adolescent wellbeing: time trends and cross-national patterns. (13th November 2019) - Morgan, A
Abstract: Since 1985, the HBSC Study has conducted 9 quadrennial surveys. There has been a growing number of HBSC participating countries over the 3.5 decades - from 5 to almost 50, in Europe and North America. In total there have been 298 national HBSC surveys and data collected from more than 1.5 million 11, 13 and 15 year olds. This paper asks - 'What have we found out about adolescent mental health' from this enormous research endeavour? 1000 papers have been published from HBSC and of these, just over 10% (120) have a primary focus on mental health. Notwithstanding the complexity of how mental health is conceptualized in each case, the 120 abstracts were scanned and empirical evidence was organised according to Bronfenbrenner's bio-ecological model in order to synthesise key findings, in order to evaluate: where there were significant contributions to knowledge/understanding of mental health; where this was limited and where real gaps existed. A vast array of topics was explored on adolescent mental health with a strong focus on the effects of bullying, the school environment and social and economic inequalities. There was a lack of attention to the importance of friendship and prosocial behaviour. Apart from parents, the role of family members, including grandparents and siblings, in supporting or negatively impacting mental health, was neglected. It was concluded that a deeper investigation is needed into behaviours and social contexts that support positive mental health. The use of the bio-ecological model helped to systematise the evidence to provide an overview of what HBSC has achieved in terms of progressing our understanding of adolescent mental health and where gaps exist. The implications of this review for HBSC's future development are considered in addition to reflection on what contribution the research to date can make to policy development to improve adolescent health internationally.